Mobility and heritage in Northern Thailand and Laos: Past and present : Proceedings of the Chiang Mai Conference, 1 - 2 December 2011 - Évrard, Olivier; Guillaud, Dominique; Vaddhanaphuti , Chayan; Keyes, Charles F. (Chiang Mai Chiang Mai University, 2013)
This volume bring together papers that were presented during the conference "Sedentism in the Mekong region: Mobility and Heritage in a long-term perspective" held at the Faculty of Social Science of Chiang Mai University. This conference presented the results of the program entitled "Sedentary settlements around the Mekong: identities, techniques, territories and environments as well as similar issues of locality, territoriality and identity.
Center for Ethnic Studies and Development. Faculty of Social Sciences. Chiang Mai University.
Keywords: Sách tham khảo